A new robotic assistance system for percutaneous CT-guided punctures: Initial experience. Issue 2 (3rd March 2016) - Groetz, Simon; Wilhelm, Kai; Willinek, Winfried; Pieper, Claus; Schild, Hans; Thomas, Daniel
Abstract: Purpose: To evaluate the feasibility of CT-guided bone biopsies using a novel robotic needle guide.Material and methods: The robotic needle guide iSYS 1.3 (iSYS Medzintechnik, GmbH, Kitzbuehel, Austria) mounted on the standard table of a CT scanner was used for all studies. For preclinical testing, eight vertebral bodies of dead swine were biopsied, trying to place the needle in the center of the vertebral body via a transpedicular access. For clinical evaluation, bone biopsies were taken in three different patients with ambiguous bone lesions. All biopsies were performed under general anesthesia, using a 12G bone biopsy needle.Results: The animal studies demonstrated that the biopsy needle could be placed accurately in the center of the vertebral body in all cases. No readjustment was necessary, the CT scans demonstrated an intrapedicular trajectory avoiding the spinal canal or the neural foramina. Subsequently, following the animal studies, all biopsies could be performed successfully. Needle placement was accurate without any need for readjustment. No complications occurred during the procedure.Conclusion: Using the iSYS 1.3 allows for accurate and simple stereotactic biopsies of bone lesions, avoiding the need for needle readjustment. The systems may offer even less experienced teams to take biopsies in regions which are difficult to access.